Web Based Aviation Communication Tool Information System - Amiruddin, Erwin Gatot (Ceddi Journal of Information System and Technology (JST), 2022)
In air transportation, communication systems play a vital role as a link between ground personnel, pilots, and other personnel on the ground. However, the process of recording maintenance and repairs of aviation communication equipment still uses conventional, paper-based methods, which are inefficient, error-prone, and require significant space for archiving. This study aims to design and implement an information system for reporting maintenance and repairs of Aviation Communication Facilities at the Makassar Branch of the Public Company (PERUM) LPPNPI, utilizing a web-based platform. Research data was obtained through field observations, data requests, and literature reviews. The system development method used the Waterfall model. The results indicate that the developed information system facilitates technicians in recording maintenance and repair reports more quickly, accurately, and in an organized manner. The system was tested using Black Box and User Acceptance Test (UAT) techniques with 20 respondents. The test results showed a feasibility rate of 85%, indicating that the system can be implemented effectively in the work environment. This innovation enhances the effectiveness of aviation communication facility management and administrative efficiency, while also supporting improved operational safety in air transportation through the availability of more transparent, accurate, and easily accessible data.